2014
DOI: 10.1007/s10551-013-2044-0
|View full text |Cite
|
Sign up to set email alerts
|

CEO Gender, Ethical Leadership, and Accounting Conservatism

Abstract: Because male CEOs dominate corporate leadership, the literature on top management decision-making suffers from an implicit masculine bias. Although research indicates that males and females are biologically and psychologically different, the leadership characteristics of female CEOs are largely unexplored. Two of these characteristics, risk aversion and ethical sensitivity, are tied to key accounting issues, such as conservatism in financial reporting and steadfast opposition to fraud. In this study, we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
267
2
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 319 publications
(295 citation statements)
references
References 111 publications
18
267
2
8
Order By: Relevance
“…This implies that the female participation exhibit higher level of accounting conservatism. This findings support the results in several previous studies (e.g., Barua et al, 2010;Peni & Vä hä maa, 2010;Ho et al, 2015), which indicate that women involvement on boards enhance board monitoring, because the female directors are more ethical and risk averse, tend to report more conservative earnings and they have the ability to recognize bad news in reported earnings in a more timely fashion. This result is consistent with Ginesti et al (2018), who found that the existence a considerable proportion of female directors on the board gives more quality and transparency for financial statements.…”
Section: Multivariate Analysissupporting
confidence: 91%
See 4 more Smart Citations
“…This implies that the female participation exhibit higher level of accounting conservatism. This findings support the results in several previous studies (e.g., Barua et al, 2010;Peni & Vä hä maa, 2010;Ho et al, 2015), which indicate that women involvement on boards enhance board monitoring, because the female directors are more ethical and risk averse, tend to report more conservative earnings and they have the ability to recognize bad news in reported earnings in a more timely fashion. This result is consistent with Ginesti et al (2018), who found that the existence a considerable proportion of female directors on the board gives more quality and transparency for financial statements.…”
Section: Multivariate Analysissupporting
confidence: 91%
“…"Using a sample of 13,206 firm years listed in the USA for a period from 1996-2008, Ho et al (2015) examined the relationship between CEO gender, ethical leadership, and Accounting conservatism. They found that there is a positive and strong relationship between CEO gender and accounting conservatism.…”
Section: Gender Diversity and Accounting Conservatismmentioning
confidence: 99%
See 3 more Smart Citations